Everyday leisure and happiness in worktown: a comparison of 1938 and 2014. Issue 4 (1st October 2016) - McHugh, Sandie; Snape, Bob; Haworth, John; Carson, Jerome
ABSTRACT: This paper presents an analytical comparison of two surveys of subjective perceptions of leisure and happiness. The first was undertaken in 1938 by Mass Observation for its ethnographic study of everyday working-class life in Bolton, or "Worktown". Leisure was found to be important to happiness insofar as it formed part of an everyday communal life, working through friendship, the appreciation of music and enjoyment of nature, reading and involvement in informal active citizenship. The second survey was undertaken in 2014 as a part-replication of the 1938 survey, using the method adopted by Mass Observation of linking a series of everyday situations and experiences to happiness. A total of 489 self-selecting respondents completed a questionnaire modelled on that used in 1938. The 2014 survey revealed a number of important continuities and differences from the survey of 1938 and the importance of leisure as an agent of happiness rose from eighth place in 1938 to third place in 2014.